Reflections on groups and organizations - Kets de Vries, Manfred F. R. (San Francisco, CA : Jossey-Bass, 2011)
Reflections on Groups and Organizations is the third and final book in the On the Couch with Manfred Kets de Vries series. Broadening the Kets De Vries canvas, this book examines concepts of organizational health, performance, and change. Material ranges from studies of high performance teams - based on time the author spent with the pygmies of central Africa - to the study of organizational stars, to the use of coaching interventions to improve personal and organizational functioning. Kets de Vries looks at the interpersonal and group processes that determine how organizatio.
pt. 1. Interpersonal and group processes -- pt. 2. The people dimension in organizations -- pt. 3. Changing people and organizations.
Includes bibliographical references (pages 313-325) and index.
Print version record.
John Wiley and Sons
Keywords: Psychology, Industrial; Organizational change -- Psychological aspects; Psychology, Industrial; Psychologie du travail; Changement organisationnel -- Aspect psychologique; Organizational change -- Psychological aspects; Psychology, Industrial